PELATIHAN TATA GERAK DAN SIKAP TUBUH DALAM LITURGI EKARISTI - Toron, Vinsensius; Lelu Beding, Skolastika (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This training aims to increase the understanding of people in the Larantuka diocese, East Flores Regency, and Lembata regarding movement and posture in the Eucharistic liturgy. The training will occur six months on weekends, from May 6 to October 28, 2023, in East Flores Regency. The training method combines theory and practice, focusing on gathering, standing, and sitting. Interactive and participatory, the training allows participants to practice and apply concepts with question-and-answer sessions and live feedback from trainers. The training results showed significant changes in the gestures and attitudes of the people when celebrating the Eucharist after basic understanding was given. This understanding creates a foundation for positive change, increases responsiveness to songs or prayers, and increases people's participation and consistency in the liturgy. In conclusion, proper education and training can enrich the quality of the celebration of the Eucharist, providing life experiences and meaning for the people.